Widths of functional classes defined by majorants of generalized moduli of smoothness in the spaces S^p - Abdullayev, F.; Serdyuk, Anatolii; Shidlich, A. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.5 We obtain exact Jackson-type inequalities in terms of best approximations and averaged values of generalized moduli of smoothness in spaces S^p. For classes of periodic functions defined by certain conditions on the averaged values of the generalized moduli of smoothness, the Kolmogorov, Bernstein, linear, and projective widths in the spaces S^p are found.